Sistem Pembelajaran Tahfidz Al-Qur’an di Pondok Pesantren Tahfidz Al-Qur’an Ibadurrohman Muara Enim - Sismaren Diyanti (MODELING: Jurnal Program Studi PGMI, 2022)
Ibadurrohman Muara Enim Islamic Boarding School is a tahfidz Qur'an-based Islamic boarding school that targets its students to complete memorizing 30 chapters of the Qur'an. However, the Islamic boarding school cannot be separated from facing various problems so that the Qur'an memorization program at the Ibadurrahman Islamic Boarding School currently has achievements that have not been maximized. This study aims to find out: 1) How is the implementation of the tahfidz Al-Qur'an learning system at the Tahfidz Al-Qur'an Islamic Boarding School Ibadurrohman Muara Enim, 2) What are the supporting factors and obstacles in implementing the learning system. This research is a field research, while the type and nature of this research is a qualitative descriptive field. This research uses interview, observation and documentation data collection techniques. The data validity technique uses technical triangulation, source triangulation and time triangulation. The results showed that the implementation of the Tahfidz Al-Qur'an Learning System at the Tahfidz Al-Qur'an Islamic Boarding School Ibadurrohman Muara Enim was the learning goal, namely to print Qur'an memorizers with noble character. Different abilities of students. Tahfidz teachers who live are hafidz hafidzoh 30 Juz Al-Qur'an. The learning material used is the Qur'an. The learning media used are print media, audio, visual, and audio visual media. Furthermore, the methods applied are the Qof method, the lecture method, the demonstration method, the talaqqi method, and the sima'i method and the muraja'ah method. And in terms of the evaluation of the tahfidz learning, an exam is held every time you finish memorizing per 1 juz, 5 juz and so on. Supporting factors in implementing tahfidz learning at Tahfidz Al-Qur'an Islamic Boarding School Muara Enim are strategic location, supportive environment, memorization goals, memorization according to ability, health, available time, methods used and motivational support. The constraining factors are infrastructure and facilities that are not maximized, lack of human resources, health, boredom, sleepiness, fullness, unstable spirit, not optimally dividing time, not knowing the right strategy, different abilities and reading the Qur'an that is not optimal. the recitation is not good yet.